2006
DOI: 10.1038/modpathol.3800587
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 and VEGF expression in the primary site and the metastatic site of human osteosarcoma: analysis within a group of patients, all of whom developed lung metastasis

Abstract: The chemokine, CXCL12, and its receptor, CXCR4, have recently been shown to play an important role in metastasis of several kinds of carcinoma. It has also been demonstrated that VEGF regulates both the expression of CXCR4 and invasiveness in breast cancer cell lines. We compared the immunohistochemical expression of CXCR4 and VEGF between the primary site and a concordant pulmonary metastatic site in 30 osteosarcoma patients, all of which had undergone thoracotomy. Microvessel density (MVD) as shown by immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
131
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(142 citation statements)
references
References 20 publications
7
131
0
4
Order By: Relevance
“…In our previous study, we found a significant positive correlation between immunohistochemical VEGF and CXCR4 expression. 22 In the current study, we also found a significant relationship between CXCR4 mRNA expression and VEGF mRNA expression in MNRCT. Therefore, VEGF may also be a candidate for a molecular target in the treatment of MNRCT, because of its close correlation with CXCR4 expression and because of its adverse effect on patient's survival in this tumor group.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…In our previous study, we found a significant positive correlation between immunohistochemical VEGF and CXCR4 expression. 22 In the current study, we also found a significant relationship between CXCR4 mRNA expression and VEGF mRNA expression in MNRCT. Therefore, VEGF may also be a candidate for a molecular target in the treatment of MNRCT, because of its close correlation with CXCR4 expression and because of its adverse effect on patient's survival in this tumor group.…”
Section: Discussionsupporting
confidence: 60%
“…23 We also demonstrated increased immunohistochemical expression of CXCR4 at the metastatic site, compared with that at the primary site in osteosarcoma. 22 In the current study, no significant difference was detected between the expression level of CXCR4 mRNA at the primary site and that at the metastatic or recurrent site.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Because many of the receptors and downstream signaling molecules are tyrosine kinases [18,22], inhibitors of these kinases are a majority of the most promising anticancer drugs [4,10,21,27]. Although osteosarcoma has not been as well studied as other types of cancer, overexpression in osteosarcoma has been reported for both growth factors and their tyrosine kinase receptors, and overexpression of some of these molecules correlates with metastasis and poor survival in patients with osteosarcoma [5,8,9,15,17,20,23,28,33,36,47,49,60,65].…”
Section: Introductionmentioning
confidence: 99%